Negotiating Race and Identity in Chimamanda Ngozi Adichie’s Americanah (International Journal of Food and Nutritional Sciences, 2022)
This paper entitled “Negotiating Race and Identity in Chimamanda Ngozi Adichie’s Americanah” critically analyses race and racism in America, England and Nigeria as depicted by the author. Race relations are the ways in which people from different races living together in the same community, behave towards each other. She also explores the race relations between the native White Americans and the Non- American Blacks especially African Americans and American Africans. The novel moves across different societies and its reflection of the global tensions. The paper discusses the mindset of the people based on colour and how it plays an important part in the life of a black in a non-white country. It also attempts to analyse various issues on race through the incidents which are presented in the novel Americanah.